Implementation of the AIDA Model in Marketing Communication Strategy for Executive Outpatient Services at a Private Hospital in Karawang - Triwahyuni, Nurul Hikmat; Nurmawaty, Dwi (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
This study analyzes the implementation of marketing communication strategies based on the AIDA model (Attention, Interest, Desire, Action) to increase patient visits to Executive Outpatient Services at Hermina Karawang Hospital in 2025. The research was driven by a 49% decline in executive outpatient visits compared to the previous year. A descriptive qualitative method with a case study approach was employed. Data were collected through in-depth interviews, observations, and document reviews, and validated using source and method triangulation. Informants included marketing staff, hospital management, and patients who had used the services. The findings indicate that at the Attention stage, social media promotions (Instagram, TikTok) and leaflets successfully attracted attention, although public understanding of service benefits remained limited. At the Interest stage, interest was fostered through comfortable facilities and fast-track services, but educational efforts were inadequate. The Desire stage showed that personalized services and exclusive facilities stimulated desire, yet cost perceptions acted as a barrier. At the Action stage, some patients utilized and recommended the service, but conversion from interest to action was suboptimal due to limited information and the absence of loyalty programs. The study concludes that applying the AIDA model enhances awareness and interest but requires stronger efforts in patient education, cost transparency, and retention strategies. It is recommended that Hermina Karawang Hospital develop educational content, testimonial-driven digital campaigns, and loyalty programs to ensure sustainable utilization of executive outpatient services.